Method for strengthening stabilization of uranium-containing waste through graded porous material
Through the mixing and oscillating curing mold technology of graded porous materials and cement, the aging and secondary pollution of uranium solid waste caused by traditional cement curing technology is solved, and the long-term stable fixation and compressive strength of uranium are achieved, which significantly reduces the migration of uranium and toxicity.
Patent Information
- Application Number
- CN202411226412.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional cement curing technology leads to the aging of uranium solid waste and the problem of secondary pollution, and requires a more effective method to stabilize uranium-containing waste.
The mixture of graded porous materials and cement is used to form a high-stable curing agent, and the mold is cured by oscillation to ensure the presence of bubbles, followed by curing under specific humidity and temperature conditions to form a stable uranium solid waste curing body.
Long-term stable fixation of uranium is achieved, the migration and toxicity of uranium is reduced, the compressive strength and long-term stability of the solidified body are ensured, and secondary pollution is avoided.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of uranium pollution solidification, and in particular relates to a method for strengthening the stabilization of uranium-containing wastes using graded porous materials. Background Art
[0002] As an important energy resource, uranium is widely used in nuclear, pharmaceutical, agricultural and defense industries. However, with the large-scale development and use of uranium resources, a large amount of uranium-containing solid waste has been generated, causing widespread pollution to the surrounding environment. Chemical toxicity is the main cause of uranium's environmental damage. Under naturally existing redox conditions, uranium mainly exists in the form of hexavalent uranium (U(VI)) and tetravalent uranium (U(IV)). The solubility, mobility and toxicity of U(VI) are higher than those of U(IV). Therefore, the harmless disposal of uranium-containing solid waste usually takes reducing migration and toxicity as the main strategy. At present, cement solidification technology is widely used in the world for the solidification of low- and medium-level radioactive waste (strontium, cesium, uranium, etc.) due to its advantages such as simple process, good heat resistance, wide source of raw materials and low investment. However, cement solidification blocks will age with changes in environmental factors, resulting in reduced cement strength and cracking, and never causing re-leaching of fixed nuclides. Therefore, it is necessary to improve the traditional cement solidification technology to achieve long-term fixation of uranium solid waste.
[0003] In summary, the stabilization treatment of uranium-containing solid waste needs to be optimized to overcome the secondary pollution caused by traditional cement solidification. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of secondary pollution caused by aging of existing cement solidified waste, and to provide a method for strengthening the stabilization of uranium-containing waste by using graded porous materials.
[0005] The specific technical solutions adopted by the present invention are as follows:
[0006] The present invention provides a method for strengthening the stabilization of uranium-containing waste using a graded porous material, which is specifically as follows:
[0007] S1: mixing a graded porous material with cement and stirring evenly to obtain a highly stable curing agent; the graded porous material has a graded pore structure on the surface and inside thereof for fixing easily mobile uranyl ions;
[0008] S2: adding the uranium-containing waste to be solidified to the high-stability solidifying agent to obtain a cement mixture; after the cement mixture is evenly mixed, placing it in a solidification mold, and shaking the solidification mold until no bubbles are generated in the cement mixture; after demolding, curing is performed to obtain a solidified body of uranium-containing solid waste.
[0009] Preferably, the volume ratio of the graded porous material to cement is 1:4.
[0010] Preferably, the graded porous material is made of defatted animal bone carbonized material.
[0011] Furthermore, the main components of the hierarchical porous material are hydroxyapatite, calcium carbonate and carbon.
[0012] Preferably, the uranium-containing waste is uranium-containing wastewater or uranium-containing solid waste.
[0013] Furthermore, in step S2, the mass ratio of the high-stability solidifying agent to the uranium-containing solid waste to be solidified is 1:(1.5-4).
[0014] Furthermore, the solid waste is uranium-containing coal ash.
[0015] Preferably, the curing conditions are set as: humidity 90-100%, temperature 20-30° C., and curing time 28-30 days.
[0016] Preferably, the liquid-to-solid ratio of the cement mixture is controlled at 0.4-0.5.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The present invention provides an efficient, long-lasting and green method for stabilizing uranium-containing solid waste by exploring the optimal ratio between graded porous materials and cement.
[0019] (2) The graded porous material prepared by the present invention can transfer uranium from solid waste to a highly stable solidifying agent, and transform uranium from an active state such as an exchangeable state and an oxidizable state to a stable state mainly composed of a residual state and a carbonate-bound state. Even if the solidified body itself is broken due to environmental factors, the uranium can still be fixed. DETAILED DESCRIPTION
[0020] The present invention is further described and illustrated below in conjunction with specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0021] Example 1
[0022] This embodiment provides a method for strengthening the stabilization of uranium-containing wastewater using hierarchical porous materials, which is as follows:
[0023] (1) Preparation of porcine tubular bone-based graded porous materials.
[0024] The pig shank was heated in a water bath at 95°C for 180 minutes to remove the residual tissue structure on the shank. This step was repeated 3 times. After the removal was completed, the bones were processed into fragments and placed in a 0.1-0.2 mol / L sodium carbonate solution for 1 day. The bones were then washed with water and dried at 105°C for 1 day. After drying, the pig bone fragments were crushed to obtain pig bone powder. The pig bone powder was pyrolyzed in a muffle furnace. The muffle furnace was heated at a rate of 10°C / min. After heating to 550°C in a nitrogen atmosphere and maintained for 120 minutes, the tail gas generated by calcination was absorbed by vaseline oil, and after cooling to room temperature, a pig shank-based graded porous material was obtained.
[0025] The test results show that the pores in the obtained pig bone-based graded porous material are mainly mesopores, with an average pore diameter of 6.99 nm and a unit pore volume of 0.26 cm. 3 / g.
[0026] (2) Preparation of solidified uranium-containing solid waste.
[0027] 10 g of the graded porous material obtained in step (1) was mixed with 40 g of cement, and the mixture was stirred continuously for 180 s in a dry state to obtain a highly stable curing agent. 20 mL of uranium-containing waste liquid with a concentration of 5 g / L was added to the highly stable curing agent, and the liquid-to-solid ratio was controlled at 0.4 to obtain a cement mixture.
[0028] Smear liquid paraffin evenly on the inner wall of the mold. The size of the mold is Φ40mm×40mm. After the cement mixture is evenly mixed, place it in a solidification mold (the uranium content in each solidified mold is 100mg), and shake the solidification mold for 180s until no bubbles are generated in the cement mixture. After the surface of the cement mixture is leveled, place it in a well-ventilated and light-proof place for 24 hours, and then demold it. After demolding, cure it for four weeks under the conditions of humidity 90-100% and temperature 20-30℃ to obtain a solidified body of uranium-containing solid waste.
[0029] Next, the solidified uranium-containing solid waste was subjected to compression resistance test, uranium stabilization test and long-term stability test.
[0030] (1) According to the national standard (GB14569.1-2011), the compressive strength of the cement solidified body after four weeks of curing was tested. During the test, the universal testing machine started loading at a loading rate of 1 KN / s until the solidified body sample broke, and the maximum pressure value F (N) was recorded. After testing, the compressive strength of the solidified body of uranium-containing solid waste obtained in Example 1 reached 24.7 MPa.
[0031] (2) After the solidified body was broken into small particles, it was tested using the BCR extraction technology, and the supernatant was extracted for analysis according to the weak acid extraction state, reducible state, oxidizable state and residual state. Among them, the residual state accounted for 90%, the other states accounted for 10%, and the exchangeable state accounted for less than 1%. This shows that the uranium in the solidified body of uranium-containing solid waste mainly exists in the form of residual state and is not easy to migrate out.
[0032] (3) The solidified body was subjected to uranium leaching experiment using TCLP (Toxicity Characteristic Leaching Procedure) method. Considering the environmental differences in different regions, this embodiment used salt and acetic acid solutions of different concentrations to conduct leaching experiments on the samples. The first extraction operation was carried out in the fourth week of solidification of the solidified body, and then the extraction was carried out in a cycle of 30 days for two cycles. Accurately weigh 2.0000g of solidified body powder sample, add 40ml of leaching agent at a liquid-solid ratio of 20:1 (ml / g), place the sample on a rotary shaker, and oscillate at 150rpm at 21-25°C for 16-20h. After the oscillation is completed, let it stand for 10min, filter and dilute the sample, and use ICP-MS to measure the uranium content in the liquid, and calculate the uranium content that can be leached in the solidified body. After 88d, the uranium leaching amount of each group was less than 0.5mg / kg. This shows that the solidified body of uranium-containing solid waste has good long-term stability and uranium is not easy to migrate out.
[0033] Example 2
[0034] This embodiment provides a method for strengthening the stabilization of uranium-containing coal ash using graded porous materials, which is as follows:
[0035] (1) The preparation of the pig shank bone-based graded porous material is the same as step (1) of Example 1.
[0036] (2) Preparation of solidified uranium-containing solid waste.
[0037] 2 g of the graded porous material obtained in step (1) of Example 1 was mixed with 8 g of cement, and the mixture was stirred continuously for 180 s in a dry state to obtain a highly stable curing agent. 40 g of uranium-containing coal ash was added to the highly stable curing agent, and water was added to obtain a cement mixture, wherein the liquid-to-solid ratio was controlled at 0.4.
[0038] Smear liquid paraffin evenly on the inner wall of the mold. The size of the mold is Φ40mm×40mm. After the cement mixture is evenly mixed, place it in a solidification mold (the uranium content in each solidified mold is 100mg), and shake the solidification mold for 180s until no bubbles are generated in the cement mixture. After the surface of the cement mixture is leveled, place it in a well-ventilated and light-proof place for 24 hours, and then demold it. After demolding, cure it for four weeks under the conditions of humidity 90-100% and temperature 20-30℃ to obtain a solidified body of uranium-containing solid waste.
[0039] The compressive strength of the solidified body of uranium-containing solid waste obtained in this embodiment is 7.5MPa; in terms of the stability of the solidified body, the stable uranium occurrence form (residue state, carbonate binding state) accounts for nearly 80%, and the exchange state is less than 1%. In terms of the long-term stability of the solidified body, the leaching rate of 88d is reduced by 47% compared with that without using graded porous materials, which has a significant effect. It shows that the method provided by the present invention also has a good solidification effect on uranium-containing coal ash.
[0040] Comparative Example 1
[0041] Compared with Example 1, the ratio of the graded porous material to cement in this comparative example is different, as follows:
[0042] 5 g of the graded porous material obtained in step (1) of Example 1 was mixed with 45 g of cement, and the mixture was stirred continuously for 180 s in a dry state to obtain a highly stable curing agent. 20 mL of uranium-containing waste liquid with a concentration of 5 g / L was added to the highly stable curing agent, and the liquid-to-solid ratio was controlled at 0.4 to obtain a cement mixture.
[0043] Smear liquid paraffin evenly on the inner wall of the mold. The size of the mold is Φ40mm×40mm. After the cement mixture is evenly mixed, place it in a solidification mold (the uranium content in each solidified mold is 100mg), and shake the solidification mold for 180s until no bubbles are generated in the cement mixture. After the surface of the cement mixture is leveled, place it in a well-ventilated and light-proof place for 24 hours, and then demold it. After demolding, cure it for four weeks under the conditions of humidity 90-100% and temperature 20-30℃ to obtain a solidified body of uranium-containing solid waste.
[0044] The compressive strength of the solidified body obtained in this comparative example is 25.1 MPa, which is slightly higher than that in Example 1. However, the proportion of uranium in the residual state in the solidified body of this comparative example is 60%, which is much lower than that in Example 1. In addition, the uranium leaching amount of 88d in this comparative example is 0.6 mg / kg, which is higher than that in Example 1. Therefore, the parameter setting in Example 1 is better than that in Comparative Example 1.
[0045] Comparative Example 2
[0046] Compared with Example 1, the ratio of the graded porous material to cement in this comparative example is different, as follows:
[0047] 15 g of the graded porous material obtained in step (1) of Example 1 was mixed with 35 g of cement, and the mixture was stirred continuously for 180 s in a dry state to obtain a highly stable curing agent. 20 mL of uranium-containing waste liquid with a concentration of 5 g / L was added to the highly stable curing agent, and the liquid-to-solid ratio was controlled at 0.4 to obtain a cement mixture.
[0048] Smear liquid paraffin evenly on the inner wall of the mold. The size of the mold is Φ40mm×40mm. After the cement mixture is evenly mixed, place it in a solidification mold (the uranium content in each solidified mold is 100mg), and shake the solidification mold for 180s until no bubbles are generated in the cement mixture. After the surface of the cement mixture is leveled, place it in a well-ventilated and light-proof place for 24 hours, and then demold it. After demolding, cure it for four weeks under the conditions of humidity 90-100% and temperature 20-30℃ to obtain a solidified body of uranium-containing solid waste.
[0049] The compressive strength of the solidified body obtained in this comparative example is 15 MPa, which is much lower than that of Example 1. The proportion of uranium in the residual state in the solidified body of this comparative example is 94%, which is slightly higher than that of Example 1. In addition, the uranium leaching amount of 88d in this comparative example is 0.45 mg / kg, which is higher than that of Example 1. Due to the addition of more graded porous materials, the leaching effect is better than that of Example 1, but the compressive strength is significantly reduced. Therefore, the parameter ratio of Example 1 is better than that of Comparative Example 2.
[0050] Comparative Example 3
[0051] Compared with Example 1, the ratio of the graded porous material to cement in this comparative example is different, as follows:
[0052] 25 g of the graded porous material obtained in step (1) of Example 1 was mixed with 25 g of cement, and the mixture was stirred continuously for 180 s in a dry state to obtain a highly stable curing agent. 20 mL of uranium-containing waste liquid with a concentration of 5 g / L was added to the highly stable curing agent, and the liquid-to-solid ratio was controlled at 0.4 to obtain a cement mixture.
[0053] Smear liquid paraffin evenly on the inner wall of the mold. The size of the mold is Φ40mm×40mm. After the cement mixture is evenly mixed, place it in a solidification mold (the uranium content in each solidified mold is 100mg), and shake the solidification mold for 180s until no bubbles are generated in the cement mixture. After the surface of the cement mixture is leveled, place it in a well-ventilated and light-proof place for 24 hours, and then demold it. After demolding, cure it for four weeks under the conditions of humidity 90-100% and temperature 20-30℃ to obtain a solidified body of uranium-containing solid waste.
[0054] The compressive strength of the solidified body obtained in this comparative example is 8MPa, which is much lower than that of Example 1. The proportion of uranium in the residual state in the solidified body of this comparative example is 95%, which is slightly higher than that of Example 1. In addition, the uranium leaching amount of 88d in this comparative example is 0.35mg / kg, which is much lower than that of Example 1. Due to the addition of more graded porous materials, the leaching effect is better than that of Example 1, but the compressive strength is significantly reduced. Therefore, the parameter ratio of Example 1 is better than that of Comparative Example 2.
[0055] Comparative Example 4
[0056] The pig bone-based material used in this comparative example is different from that in Example 1, as follows:
[0057] The pig shank was heated in a water bath at 95°C for 180 minutes to remove the residual tissue structure on the shank. This step was repeated 3 times. After the removal was completed, the bones were processed into fragments and placed in a 0.1-0.2 mol / L sodium carbonate solution for 1 day. The bones were then washed with water and dried at 105°C for 1 day. After drying, the pig bone fragments were crushed to obtain pig bone powder. The pig bone powder was pyrolyzed in a muffle furnace. The muffle furnace was heated at a rate of 10°C / min. After heating to 350°C in a nitrogen atmosphere and maintained for 120 minutes, the exhaust gas generated by calcination was absorbed by vaseline oil and cooled to room temperature to obtain a pig shank-based material. After testing, the unit pore volume of the material was only 0.0058cm 3 / g, no obvious pores exist.
[0058] The above-mentioned pig bone-based material was used to prepare a solidified body of uranium-containing solid waste, and the specific steps were as described in step (2) of the embodiment. The compressive strength of the obtained solidified body was 23.5 MPa, slightly lower than that of Example 1. The proportion of uranium in the residual state in the solidified body was 85%, slightly lower than that of Example 1. The 88d uranium leaching amount was 1.1 mg / kg, much higher than that of Example 1. Therefore, it is shown that the graded porous material in Example 1 has a good effect of solidifying uranium.
[0059] Comparative Example 5
[0060] The difference between this comparative example and Example 1 is that no graded porous material is added, and the rest are the same.
[0061] The compressive strength of the solidified body obtained in this comparative example is 22.6 MPa, which is lower than that in Example 1. The proportion of residual uranium in the solidified body is 51%, which is much lower than that in Example 1. The 88d uranium leaching amount is 0.65 mg / kg, which is higher than that in Example 1. Therefore, it is shown that the graded porous material in Example 1 has a better effect of solidifying uranium.
[0062] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for strengthening the stabilization of uranium-containing waste using graded porous materials, characterized in that: The details are as follows: S1: mixing a graded porous material with cement and stirring evenly to obtain a highly stable curing agent; the graded porous material has a graded pore structure on the surface and inside thereof for fixing easily mobile uranyl ions; S2: adding the uranium-containing waste to be solidified to the high-stability solidifying agent to obtain a cement mixture; after the cement mixture is evenly mixed, placing it in a solidification mold, and shaking the solidification mold until no bubbles are generated in the cement mixture; after demolding, curing is performed to obtain a solidified body of uranium-containing solid waste.
2. The method for strengthening stabilization of uranium-containing waste by using hierarchical porous materials according to claim 1, characterized in that: The volume ratio of the graded porous material to cement is 1:
4.
3. The method for strengthening stabilization of uranium-containing waste by using hierarchical porous materials according to claim 1, characterized in that: The graded porous material is made of defatted animal bone carbonized material.
4. The method for strengthening stabilization of uranium-containing waste by using hierarchical porous materials according to claim 3, characterized in that: The hierarchical porous material mainly comprises hydroxyapatite, calcium carbonate and carbon.
5. The method for strengthening stabilization of uranium-containing waste by using hierarchical porous materials according to claim 1, characterized in that: The uranium-containing waste is uranium-containing wastewater or uranium-containing solid waste.
6. The method for strengthening stabilization of uranium-containing waste by using hierarchical porous materials according to claim 5, characterized in that: The mass ratio of the high-stability solidifying agent to the uranium-containing solid waste to be solidified in step S2 is 1:(1.5-4).
7. The method for strengthening stabilization of uranium-containing waste by using hierarchical porous materials according to claim 5, characterized in that: The solid waste is uranium-containing coal ash.
8. The method for strengthening stabilization of uranium-containing waste by using hierarchical porous materials according to claim 1, characterized in that: The curing conditions are set as: humidity 90-100%, temperature 20-30° C., and curing time 28-30 days.
9. The method for strengthening stabilization of uranium-containing waste by using hierarchical porous materials according to claim 1, characterized in that: The liquid-to-solid ratio of the cement mixture is controlled at 0.4-0.5.
